Analisis Yuridis Pidana terhadap Malpraktik Anestesi dalam Operasi Plastik di Klinik Kecantikan - Sifa Agustina Nurbani; Raden Arif Awangga (PT Elaborium Elevasi Indonesia, 2026)
The rapid development of the aesthetic industry in Indonesia has led to a significant increase in invasive medical procedures, including the administration of anesthesia in plastic surgery procedures at aesthetic clinics. This condition gives rise to legal implications when such procedures are performed without complying with professional standards, legal authority, and patient safety principles, thereby potentially constituting medical malpractice with criminal consequences. This study aims to analyze the construction of criminal liability of medical personnel and aesthetic clinics in cases of anesthesia malpractice, examine criminal sanction mechanisms under Indonesian positive law, and identify normative gaps affecting legal protection and legal certainty for patients. This research employs a normative juridical method with statutory, conceptual, and case approaches through the analysis of the Criminal Code, Law Number 1 of 2023, Law Number 17 of 2023 concerning Health, Government Regulation Number 28 of 2024, and relevant case studies of alleged anesthesia malpractice in aesthetic clinics. The results indicate that anesthesia procedures performed without adherence to professional standards (lex artis), competence, and lawful authority constitute professional negligence (culpa professionalis) that may give rise to criminal liability when the elements of unlawful conduct, fault, harmful consequences, and causal relationship are fulfilled. Such criminal liability may be imposed not only on medical personnel as individual legal subjects but also on aesthetic clinics as corporate entities based on the principle of corporate criminal liability. This study concludes that although the criminal health law framework has provided a legal basis for criminal liability in anesthesia malpractice, normative gaps remain regarding the limits of anesthesia authority in aesthetic clinics. Therefore, regu